Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada Peternakan Ayam “Subur PS” Pekanbaru - Syafrina, Nova; Yapentra, Arhipen (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research was conducted to determine the influence of work environment on employee performance at Subur PS Poultry Farm Pekanbaru. To achieve this objective, the study was conducted using a sample of 55 respondents through a questionnaire method. The data analysis employed both descriptive and quantitative methods utilizing simple linear regression. Based on the testing results of the work environment variable (X) and employee performance variable (Y) using SPSS software, the obtained t-count (6.695) was greater than the t-table value (2.006), thus indicating that variable X or the work environment factor has a positive and significant influence on employee performance at Subur PS Poultry Farm Pekanbaru. The R Square (R²) value of 0.463 (46.3%) demonstrates that employee performance at Subur PS Poultry Farm Pekanbaru can be explained by the work environment factor at 46.3%. Meanwhile, the remaining 53.7% represents other independent variables not observed in this study.